Local authorities approach in dealing with illegal building structure in residential house at Perak State / Mohammad Asyraf Ikhwan Helmi - Helmi, Mohammad Asyraf Ikhwan (2021)
The study of this research explored about Local Authorities Approach in Dealing with Illegal Building Structure in Residential House at Perak State. During this pandemic Covid-19, it is limits to approach and get the data from Local Authority cause the Movement Control Order (MCO). However, the questionnaire survey also provides to selected Local Authority based on the finding question. The problem statement of the research for the illegal building structure is the building are constructed without the permission of local authorities that can trigger problems with development planning, how local authorities solve the issue of illegal construction and the issue of amended plans without obtaining local authority approval. The aims and objective have been prepared to achieve the research goals. The researcher setting up these objectives, the aim of the research becomes easily to understand and all the data that been obtained from all the resources. The objective for this study is to identify the common type of illegal building structure at residential house and to analyse Local Authority awareness to prevent illegal building structure at residential area. There were about 30 respondent who are participate in this research and the questionnaire were distributed for a data generation. The data is analysed using quantitative method. As for this research study, the objectives have been achieved by obtaining the data from the questionnaires survey. The recommendations are made for the future researchers to be more through on the data collection once the country back to normal from the pandemic.